Peningkatan Kapasitas UMKM PT Semen Indonesia Gresik Melalui Standarisasi dan Branding Digital - Nurul Khaira; Dunga Dwi Barinta; Jovi Sulistiawan; Yetty Dwi Lestari (Penerbit Goodwood, 2026)
Purpose: This community service program aims to strengthen the competitiveness of PT Semen Indonesia’s fostered Usaha Mikro, Kecil, dan Menengah (UMKM) by improving their skills in digital marketing, implementing simple Standard Operating Procedures (SOPs), and enhancing product branding, packaging, and presentation to support better business performance. Methodology: The program was conducted at the Sentra Kuliner/Pujasera Gresik involving 26 UMKM owners under PT Semen Indonesia’s guidance. The activities included training workshops, demonstrations, mentoring sessions, pre-test and post-test assessments, and field observations. Supporting tools such as presentation materials, social media examples, SOP templates, and packaging samples were used to facilitate the learning process. Results: The program improved participants’ understanding, especially in SOP development, digital marketing, and product presentation, though some gaps in digital literacy and creative design remained. Conclusions: The program strengthened managerial, operational, and marketing skills of the 26 UMKM participants; ongoing mentoring is recommended for lasting impact. Limitations: Short program duration, small sample, and no long-term impact measurement. Contributions: Demonstrates that integrated training in SOP, digital marketing, and branding enhances UMKM capabilities and supports effective empowerment.